Analisis Keputusan Pembelian Konsumen Berdasarkan Bauran Pemasaran pada Produk Soft Cookies di Kaje Nibbles Jakarta - Jinan Ashilla Timur; Ari Fadiati; Guspri Devi Artanti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
The culinary business is one of the rapidly growing sectors with potential for continuous expansion. This study aims to analyze the purchasing decisions of soft cookies products through a marketing mix survey at Kaje Nibbles Jakarta. Data collection for this research utilized a questionnaire in the form of a Google Form containing 19 statements that have passed validity and reliability tests. The marketing mix instrument consists of four indicators: Product, with sub-indicators including product quality, product design, and packaging. Price, with sub-indicators such as price appropriateness to product quality, price appropriateness to benefits, price competitiveness, and affordability. Place, with sub-indicators including accessibility, visibility, traffic, and parking. Promotion, with sub-indicators including advertising, sales promotion, and public relations. The questionnaire was distributed to Kaje Nibbles consumers through online channels. The research data will be presented descriptively through statistical analysis. Based on the findings, the researcher will explain the situation and conditions according to the data obtained. The results indicate that on average, the highest scoring culinary interest indicator is in the promotion category, specifically public relations, while the lowest scoring indicator is in the product category, specifically product design.